Receiving information about rice seeds on mobile phones in eastern India. Issue 1 (2nd January 2018) - Pede, Valerien; Yamano, Takashi; Chellattanveettil, Prakashan; Gupta, Ishika
ABSTRACT: This article examines how farmers use mobile phones to obtain information about rice varieties in eastern India and investigates if this contributes to rice varietal replacement. The findings show that farmers located farther away from the market were more likely to pay for the calls. Moreover, about 26% of the farmers who had to pay to receive calls purchased seeds of at least one rice variety that they had never planted before, while less than 16% of farmers who received no calls did so. Regression results confirmed that paying charges to receive rice varietal information is associated with varietal replacement.